조선후기 왕과 왕법 : 정조대 왕법에 관한 정치주체들의 인식을 중심으로 - 이하경(Lee, Hakyoung) (한국학(구 정신문화연구), 2023)
이 연구의 목적은 조선후기 정조(正祖, 재위 1776~1800)대 왕법에 대한 정치 주체들의 인식을 살펴봄으로써, 전근대 시기 왕법의 정치적인 의미와 속성을 구체화하는 데에 있다. 특히, 정조 즉위년의 홍술해(洪述海) 사건과 즉위년부터 논란이 되었다가 정조 23년에 마무리된 화완옹주(和緩翁主) 사건을 중심으로, 정조와 신하들이 사법적 판단을 내리는 과정에서 왕과 신하가 왕법을 어떻게 전유하고 있는지를 추적했다. 선행연구에서는 정조 대에 이루어진 법전 편찬, 형정 정비와 같은 법 제도적 측면의 발전에 주목하거나, 정조의 사법 추론 과정에서의 나타나는 나름의 합리성을 근거로 정조를 법치의 시대로 재평가하기도 하였다. 반면, 이 연구에서는 당대의 맥락 속에서 정조의 사법 판단과정을 재고해야 한다고 보고, 왕법에 대한 정치 주체들의 인식에 주목했다. 우선, 정조 시대에 활용되고 있는 왕법의 개념을 두 차원으로 구별해 내었다. 왕의 명령이 수교의 형태로 법률적인 효과를 갖는 개별 왕법과 이러한 개별 왕법이 모여 일정한 형태로 성문법이 되고 이후 이 모두를 아우르는 추상적인 하나의 법체계로서의 왕법이다. 이러한 개념적 분석을 바탕으로 홍술해 사건과 화완옹주 사건 등을 중심으로 정조 대 왕법의 적용을 둘러싼 다양한 사례연구를 통해서, 한편으로는 정조의 일견 모순적으로 보이는 사법 판단 과정을 분석하고, 다른 한편으로는 최종적인 사법 판단을 내릴 때의 정치 과정의 중요성을 강조했다. This study aims to delineate the political meaning and characteristics of the royal law by analyzing political actors’ perceptions in the judicial cases under King Jŏngjo’s reign during the late Chosŏn period. Particularly, this research traces how the royal law was understood and appropriated by political actors, analyzing diverse cases, including the Hongsurhae Case (1776) and Hwawanongju Case (1799). Studies on King Jŏngjo have revealed the development of the legal system, highlighting legal codifications and judicial reforms, or have attempted to reassess King Jŏngjo’s reign as an era of the rule of law based on the King’s legal reasoning. This study, however, argues the reconsideration of King Jŏngjo’s judicial process in its historical context. King Jŏngjo emphasized the impartial enforcement of the royal law, although his judicial decisions were not always in accordance with the royal law. To analyze this seemingly contradictory judicial judgment process of King Jŏngjo, this study distinguishes two dimensions of the concept of the royal law: individual royal law, wherein the king’s orders had legal effects; and systematic royal law, which refers to a more abstract legal system encompassing all kinds of rules and codes. Based on this conceptual analysis, this study examines various judicial cases related to the application of the royal law during King Jŏngjo’s reign. Additonally, it emphasizes the significance of the political process in final judicial decisions. KCI Citation Count: 0